High dose subcutaneous immunoglobulin for idiopathic inflammatory myopathies and dysimmune peripheral chronic neuropathies treatment: observational study of quality of life and tolerance. (3rd June 2017) - Hachulla, E.; Benveniste, O.; Hamidou, M.; Mouthon, L.; Schleinitz, N.; Lozeron, P.; Léger, J.M.; Vial, C.; Viala, K.
Abstract : Background : In patients with autoimmune diseases who still derive benefit from high dose intravenous immunoglobulin (IVIg) treatment, some physicians resort to subcutaneous (SC) Ig as a replacement therapy. Objective : To collect quality of life (QoL) and tolerance data on SCIg in patients for whom the switch from IVIg to SCIg is essential to maintain treatment. Methods : This observational study included patients with either idiopathic inflammatory myopathies (IIM) or chronic dysimmune peripheral neuropathies (CDPN) treated with IVIg, who had been switched to SCIg administration for at least three months. The main objective was to describe the impact of SCIg on QoL after six months, using the generic Short-Form 36 questionnaire (SF-36). The secondary objectives were to evaluate SCIg tolerance and clinical efficiency. Results : Eight centres recruited 12 IIM patients and two centres recruited 11 CDPN patients. Neither the physical nor the mental health SF-36 component summaries showed any QoL deterioration during the six-month study period and all IIM and CDPN patients remained clinically stable during the same period. The most frequent adverse effects were injection site reactions (50%), cutaneous tissue disorders (18.2%), and nervous system disorders (13.6%). Two serious adverse events (myocarditis and cerebrovascular accident) occurred in two patients. Conclusion : In these rare inflammatory diseases, high dose SCIg administration (which can be home based) has no deleterious effect on patient QoL. It appears to be a safe and efficient alternative to hospital-based IVIg.